Settlement Of Medical Disputes Through Restorative Justice According To Law No. 17 Of 2023 Concerning Health - Rudy Adiputra; Erikson Sihotang; Ni Ketut Wiratny (Journal of Social Research, 2024)
Settlement of Medical Disputes through litigation and non-litigation, a special institution which functions as a legal institution whose function is to resolve disputes, the Ethics Committee of the Indonesian Medical Discipline Honorary Council (MKDKI) was formed, the Medical Ethics Honorary Council (MKEK) Dispute Settlement through the Consumer Dispute Resolution Agency (BPSK) ). The Health Law Settlement contains various new provisions in the health sector, including procedures for resolving disputes in the medical and health sectors, prioritizing restorative justice as stated in Article 310 of Law no. 17 of 2023 Obstacles in restorative care that can arise are a lack of commitment from the parties involved in resolving a dispute peacefully, the patient insisting on defending his report/lawsuit, the process outside the court is deemed unable to realize the sense of justice that the victim desires. There is no special institution that acts as a legal institution whose function is to resolve medical disputes. to carry out settlements outside the court process.